Pengembangan Aplikasi Pencarian Pembantu Rumah Tangga berbasis Android - Ilham Harazki; Agi Putra Kharisma; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The search for housekeepers on life is now a common thing for some people. It is not closed the possibility that housekeepers are also looking for employers who want to hire them. High time intensity also makes employers difficult to find suitable workers because of the absence of time. Therefore, research is developed based on the problems that have been raised. In the development of search housemaid, model prototyping is used to get the necessary needs in application development. This developed application will be excavated needs to be used to create useful applications for prospective employers and prospective housekeepers. In the use of this method there is a mockup created as a picture of the application to be used, the mockup will be evaluated by the user and will be reviewed either the addition of the need or reduction of needs until the discovery of the completed application in the evaluation and will be implemented using Android. Android is an operating system that is widely used among people nowadays, development of this application using Android Studio application with database using Google Firebase Realtime database. Testing of the application there are three Tests namely Blackbox testing, usability testing, and compatibility testing, which results from the three tests are useful to make the application run as function, accepted in all actors and can run on many types of Android operating systems.